Analysis Of Preventive Measures On Sailing Safety In Indonesia (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Based on data from the National Transportation Safety Committee (KNKT), 178 accident cases have been investigated from 2018-2023. Of the 178 cases, 102 cases were classified as very serious cruise ship accidents (very serious marine accidents) and 76 cases were classified as incidents. This research aims to analyze preventive measures for shipping safety in Indonesia. This research is a type of qualitative research with qualitative descriptive analysis methods and literature reviews.
Keywords: Preventive Actions, shipping safety, shipping accidents